LITHUANIAN BOOK AUTHORS DURING THE PERIOD OF PRESS BAN - STEPONAITIENĖ, JOLITA (Knygotyra, 2010)
In 1864, press in the Latin alphabet was banned in Lithuania. This ban lasted until 1904. Despite all the efforts of the tsarist administration, banned books printed in Lithuania Minor and the United States of America reached readers of Lithuania Major. During 40 years, a new generation of Lithuanian books’ authors developed. It was caused by the growth and expansion of national movement and the nation’s consciousness in the ninth decade of the 19th century. After 1883 when the monthly public political and literary newspaper “Austra” in the Lithuanian language began being published, the number of Lithuanian book authors increased by 4–6 new names every year, while until the appearance of this newspaper this number was only 1–2 and not annually.The basis of the new generation’s authors was formed under the new circumstances, i.e after the press ban, by people with secular professions and occupations, not only those who had graduated from universities, institutes or seminaries, but also those who had finished only several classes and were self-educated. Due to the different economic and social conditions, access to education, most authors were from Suvalkija and East Aukštaitija. For this reason, the written language dialect changed. During this period, among the Lithuanian authors also women appeared.